2023
DOI: 10.1126/sciadv.abo7605
|View full text |Cite
|
Sign up to set email alerts
|

DNA dioxygenases Tet2/3 regulate gene promoter accessibility and chromatin topology in lineage-specific loci to control epithelial differentiation

Abstract: Execution of lineage-specific differentiation programs requires tight coordination between many regulators including Ten-eleven translocation (TET) family enzymes, catalyzing 5-methylcytosine oxidation in DNA. Here, by using Keratin 14 – Cre –driven ablation of Tet genes in skin epithelial cells, we demonstrate that ablation of Tet2/Tet3 results in marked alterations of hair shape and length followed by hair loss. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…In this case, a putative superenhancer in one TAD activates target genes in the other TADs illustrating that, in at least some genome loci, TAD boundaries insulate large chromosome segments from each other but cannot prevent distant regulatory interactions. Recently, it has been shown that such distant contacts within mouse keratin locus are regulated by DNA deoxygenases Tet2/3 in a DNA methylation-dependent and DNA methylation-independent manner [ 234 ]. These data are of particular interest because they raise questions about the potential modulation of keratin gene expression by artificial recruitment of DNA-methyltransferases [ 235 ].…”
Section: Chromatin Spatial Organization As a Regulator Of Keratin Gen...mentioning
confidence: 99%
“…In this case, a putative superenhancer in one TAD activates target genes in the other TADs illustrating that, in at least some genome loci, TAD boundaries insulate large chromosome segments from each other but cannot prevent distant regulatory interactions. Recently, it has been shown that such distant contacts within mouse keratin locus are regulated by DNA deoxygenases Tet2/3 in a DNA methylation-dependent and DNA methylation-independent manner [ 234 ]. These data are of particular interest because they raise questions about the potential modulation of keratin gene expression by artificial recruitment of DNA-methyltransferases [ 235 ].…”
Section: Chromatin Spatial Organization As a Regulator Of Keratin Gen...mentioning
confidence: 99%